Die volkskerkvoorstelling in die Kerkwet van die Nederduitsch Hervormde Kerk van Afrika - Koekemoer, J. H. (Hervormde teologiese studies, 1987)
The term Volkskerk in the Church Order of the Nederduitsch Hervormde Kerk van AfrikaThe Nederduitsch Hervormde Kerk states in its Church Order that it is a volkskerk(people's church). In this article the term volkskerk and the historical line of how it came to use in the Nederduitsch Hervormde Kerk, is researched. In the light of these statements the term volkskerk and its meaning in the contemporary Order of the Nederduitsch Hervormde Kerk, is dealt with.